The Effect of Special Exercises Using Variable Aid on the Development of Endurance (Speed, Strength) and 100m Freestyle Swimming Achievement in Handicapped Men Class 9S - mohammed , Yaser; Sabeeh , Yasar (Journal of Physical Education, 2022)
The research aimed at designing special exercises for developing strength and speed endurance and 100m freestyle swimming achievement in handicapped men class 9S. The researchers used the experimental method with a training program applied on (5) classified players for 100m freestyle swimming while the pilot study subjects were (5). All training sessions were supervised directly by the swimmers with the assistance of team coaches. The training program included 8 weeks preparation phase with three sessions per week. The data was collected and treated using SPSS to conclude that the exercises have significant effect on the development of 100m freestyle swimming. Special exercises using aids have positive effect on the development of speed and strength endurance and 100m swimming achievement in handicapped men class 9S. Finally, the researchers recommended using resistance exercises for developing strength and speed endurance for short distances.